Higher education, economic inequality and social mobility: Implications for emerging East Asia. (November 2018) - Marginson, Simon
Highlights: There are world-wide tendencies to the growth of participation in higher education, and in many countries, 'World-Class Universities'. In many countries notably the US—social mobility is not improving despite high participation in higher education. Educational participation in the United States is highly stratified in terms of social value. Expanding higher education systems in East Asia are associated with growth in absolute social mobility, but is there more equal opportunity? A key issue in East Asia is the quality of mass higher education below the WCU layer. Abstract: Higher education systems in the Chinese civilizational zone (East Asia) are rapidly improving in quantity and quality, associated with the growth of middle classes and absolute social mobility. But are they contributing to more equal opportunities between students with different backgrounds, and greater relative social mobility? The article reviews the case of the United States, where expansion of the middle-class growth and social mobility via education in the 1950s/1970s was followed in the 1980s and after by a marked increase in inequality in incomes and higher education, and less social mobility. Will this same reversal occur in China and Korea?